Heterogeneity of blastomycosis‐like pyoderma: A selection of cases from the last 35 years. (17th January 2016) - Scuderi, Salvatore; O'Brien, Blake; Robertson, Ivan; Weedon, David
Abstract: Blastomycosis‐like pyoderma is a form of pyoderma with variable clinical findings and histopathological features. We present a case series of 39 patients collected over a 35‐year period to demonstrate its clinical features and histological findings. The most common clinical presentations found were solitary plaques, solitary nodules, sinuses, crypts, verrucous plaques and discharge, usually on sun‐exposed skin. The most common histopathological findings were chronic granulomatous inflammation, suppurative inflammation, sinus and abscess formation, pseudoepitheliomatous hyperplasia, transepidermal elimination and scarring. We discuss its treatment and the recent literature that has focused on its response to acitretin.